All Days 2012
DOI: 10.2118/162648-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Empirical Decline Curve Methods for Shale Wells

Abstract: Analyzing shale wells using traditional decline curve methods is problematic because of the nature of reservoir properties and flow behavior in typical shale wells. New empirical methods were developed to model the special production decline of shales. These methods were formulated using different mathematical and statistical bases and result in different forecasts. Hence, engineers have a variety of methods that may give different estimates for ultimate recovery when analyzing shale wells. In this work, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 12 publications
0
53
0
2
Order By: Relevance
“…The advantages of these decline curves lie in their strong empirical compliance and ease of use. Some important properties of the hyperbolic and the stretched exponential curves are expressed in Table 1, from Valkó (2009), Hö ö k et al (2014), Satter et al (2008) and Kanfar (2013). Q(t) is the cumulative production at time t, and EUR is the estimated ultimate recovery of the well.…”
Section: Decline Curve Selectionmentioning
confidence: 99%
“…The advantages of these decline curves lie in their strong empirical compliance and ease of use. Some important properties of the hyperbolic and the stretched exponential curves are expressed in Table 1, from Valkó (2009), Hö ö k et al (2014), Satter et al (2008) and Kanfar (2013). Q(t) is the cumulative production at time t, and EUR is the estimated ultimate recovery of the well.…”
Section: Decline Curve Selectionmentioning
confidence: 99%
“…Their results show that the PLE model does not appear to provide any significant tangible advantage over the MHD model. Kanfar and Wattenbarger [12] proved that the PLE model is reliable for linear flow, bilinear flow followed by linear flow, and linear flow followed by BDF, or bilinear flow followed by linear flow and finished with BDF flow. Meyet et al [28] illustrated that the PLE model varies the least with respect to length of production history for all wells, and the PLE and LGA models usually return similar results.…”
Section: Power Law Exponential Decline Modelmentioning
confidence: 99%
“…Kanfar and Wattenbarger [12] showed that the Duong model is more accurate for linear flows and bilinear-linear flows. Meyet et al [28] showed that the EURs determined with PLE and Duong model vary the least with respect to the length of production history for all wells among all of the DCA methods in their study, and other DCA methods tend to converge towards the modified Duong model and PLE model.…”
Section: Duong Modelmentioning
confidence: 99%
See 2 more Smart Citations